2016
DOI: 10.1136/jnnp-2016-314600
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal pressure and spinal cord perfusion pressure predict neurological outcome after traumatic spinal cord injury

Abstract: Surgery Following bony realignment and posterior fixation, the ISP probe (Codman, Depuy Synthes, Leeds, UK) was tunnelled through skin into the wound cavity. Under the operating microscope, the dura was opened one level below the injury. The ISP probe was inserted through the durotomy and placed on the spinal cord surface (Fig. 1A) Data collection Neurological examinations were done pre-operatively (day of injury) and at 9-12 months. Whole spine CT and MRI were done on admission and another CT within 48hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 4 publications
1
71
0
2
Order By: Relevance
“…The chance of AIS grade conversion at 9-12 months after the TSCI negatively correlates with the mean ISP on admission and positively correlates with the mean SCPP on admission (Fig. 3) [43]. Increasing SCPP presumably reduces ischemia at the injury site.…”
Section: Therapies Based On Isp Monitoringmentioning
confidence: 96%
“…The chance of AIS grade conversion at 9-12 months after the TSCI negatively correlates with the mean ISP on admission and positively correlates with the mean SCPP on admission (Fig. 3) [43]. Increasing SCPP presumably reduces ischemia at the injury site.…”
Section: Therapies Based On Isp Monitoringmentioning
confidence: 96%
“…It was of belief that bony decompression with laminectomy released the spinal epidural veins which had become congested and had inhibited the free flow of CSF, and dural decompression can be used in the prevention of high ISP [17]. Papadopoulos also demonstrated that high ISP and low SCPP are associated with injury site ischaemia, which likely causes secondary damage [18]. In patients with extensive swelling from spinal cord injury, durotomy can relieve the blockage of spinal epidural veins and arterioles of the cord, as well as relieve secondary injury [19].…”
Section: Discussionmentioning
confidence: 99%
“…Time series are also used to identify correlations with biological meaning e.g. higher ISP correlates with worse neurological outcome 13 , when ISP increases then sPRx increases (impaired autoregulation) 1,8 and tissue lactate to pyruvate ratio also increases (increased tissue ischemia) 12 Unlike ISP monitoring for TSCI, ICP monitoring for severe TBI has been the standard of care in developed countries for many years 21,22 . The early management of patients with TBI is focused on limiting secondary injury by reducing ICP below 25 mmHg and increasing CPP above 60 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Second, intervention to increase SCPP in TSCI patients improves neurological status in some patients 1 . Third, lower mean ISP and higher mean SCPP correlate with improved long-term neurological outcome 13 . Fourth, intervening to increase SCPP increases the amplitude of motor evoked responses monitored from below the injury site in some patients 1 .…”
Section: Introductionmentioning
confidence: 92%